Improvement of Hanwoo (Korean beef cattle) by selecting a giant cow and applying ovum pick-up and in vitro production technologies - Yeon-Gil Jung; Seungki Jung; Hyonsok Sol; Yeonsub Jung; Na Ahn; Sangho Roh (Journal of Animal Reproduction and Biotechnology)
Background: This study was conducted to increase meat production by 30% compared to the present by selecting a giant cow over 1,000 kg and applying biotechnologies. Methods: After OPU from 1,100 kg of giant cow, the calves were produced in Hanwoo surrogate mothers. Among 23 calves six male heads were selected, three heads of them were chosen as candidate sires, and the rest three heads were raised for 30 months for performance test. The semen of three candidate sires from the age of 22 months were collected and frozen, and the calves were produced by artificial insemination. The calf was raised to the age of 30 to 33 months and performed a progeny test. Results: The average birth weight of 23 calves born by transferring giant cow-derived embryos was 42.8 kg, and the average weight of carcass from three bulls was 615.3 kg in the performance test. In the progeny test, the average birth weight of calves born after artificial insemination of semen from giant cow-derived candidate sires was 41 kg, and the average weight of carcass after raised to the age of 30 to 33 months was 562.7 kg. As a result of performance and progeny tests, it is 148 and 96 kg higher in giant cow-derived beef cattle than the average carcass (467 kg) from general Hanwoo cattle, respectively. Conclusions: This study will have laid a great foundation for the future improvement of the Korean beef industry.